Principal Leadership and Administrative Management: A Key to Improving Educational Quality in Schools - Alifia, Larasati; Bafadal, Ibrahim; Juharyanto, Juharyanto (Proceedings Series of Educational Studies, 2024)
Education in Indonesia faces various challenges in an effort to improve its quality, which is greatly influenced by the leadership of school principals and the management of administrative staff. This study aims to analyze the contribution of these two elements in efforts to improve the quality of education. The method applied in this research is a literature study, by collecting data from various articles and relevant research. The findings show that the synergy between the principal's leadership with a clear vision and effective administrative management is crucial to creating a supportive learning environment. The conclusion of this study emphasizes the importance of harmonious collaboration between principals and administrative staff in improving the effectiveness of school operations, which in turn contributes to improving the overall quality of education. Therefore, capacity building and communication between the two parties should be continuously improved to achieve better educational goals.